Almost nothing the 20th century art and life of Józef Czapski - Karpeles, Eric 1954- (New York Review Books, 2018)
"Józef Czapski (1896-1993) lived many lives--as a soldier, public figure, historical witness, memoirist, essayist, and painter. His ninety-six years nearly span the twentieth century in its entirety. He was a student in St. Petersburg during the Russian Revolution and a painter in Paris in the Roaring Twenties. As a Polish reserve officer fighting against the invading Nazis in the opening weeks of the Second World War, he was taken prisoner by the Soviets and survived the Katyn Massacre. He never returned to Poland, working tirelessly in Paris to keep awareness of the plight of his homeland alive, overrun by totalitarian powers. Czapski was a towering public figure, but painting gave meaning to his life. Eric Karpeles, also a painter, reveals Czapski's full complexity, pulling together all the threads of this remarkable life"--
1811
Keywords: Czapski, Józef -- 1907-; Czapski, Józef / 1896-1993; Painters / Poland / Biography; Authors, Polish / 20th century / Biography; BIOGRAPHY & AUTOBIOGRAPHY / Artists, Architects, Photographers; ART / European; Authors, Polish; Painters; Poland; BIOGRAPHY & AUTOBIOGRAPHY / LGBT.; 1900-1999; Biographies; Biography; Biografie